2020
DOI: 10.1186/s12889-020-08697-3
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation and the US Ebola communication crisis: analyzing the veracity and content of social media messages related to a fear-inducing infectious disease outbreak

Abstract: Background The Ebola communication crisis of 2014 generated widespread fear and attention among Western news media, social media users, and members of the United States (US) public. Health communicators need more information on misinformation and the social media environment during a fear-inducing disease outbreak to improve communication practices. The purpose of this study was to describe the content of Ebola-related tweets with a specific focus on misinformation, political content, health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 39 publications
2
73
0
3
Order By: Relevance
“…Similar results were described for other pandemics, such as for 2009 H1N1 [17] and 2014 Ebola outbreaks. Interestingly, data from the Ebola crisis showed that statements that were political in nature were particularly at risk to spread misinformation [18]. However, to our knowledge, few studies have explored the role of information dissemination through social media on clinicians and other healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were described for other pandemics, such as for 2009 H1N1 [17] and 2014 Ebola outbreaks. Interestingly, data from the Ebola crisis showed that statements that were political in nature were particularly at risk to spread misinformation [18]. However, to our knowledge, few studies have explored the role of information dissemination through social media on clinicians and other healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…This, on one hand, is coherent with the purpose of social media themselves but, on the other hand, it entails a broader shift in how professionals conceive the access to medical information, technological advances and scientific knowledge. We believe that it is important to acknowledge this phenomenon, as well as the risk of spreading misinformation, fear or research exceptionalism, with potentially dangerous consequences for public health [ 5 , 12 , 13 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation has worsened during the COVID-19 pandemic, with misinformation about the origin of the disease, risk factors, use of chloroquine and ibuprofen, in addition to an unclear perception of the pandemic data [14][15][16]. Also to be considered is the increase in depression and anxiety generated by the COVID-19 pandemic, exacerbated by continued overexposure to information about the disease, which has also been evidenced in other epidemics such as Ebola virus [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, nine were veri ed to be accurate (Samaan et al, 2005). During the West African Ebola virus epidemic in 2014, there was widespread fear and attention among the United States-based users, followers of Western media, and social media platforms such as Twitter (Sell et al, 2020).…”
Section: Public Health Disasters and Misinformationmentioning
confidence: 99%